2008
DOI: 10.1080/10826080701202429
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Protracted Withdrawal Syndrome: The Role of Anhedonia

Abstract: The results of this study suggest the relevance of protracted withdrawal well beyond the limited period following the abrupt cessation of alcohol intake. The clinical dimension of anhedonia cannot be separated from the other behavioral symptoms of withdrawal and should be considered as part of the same process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(66 citation statements)
references
References 37 publications
(32 reference statements)
4
62
0
Order By: Relevance
“…Additionally, ADs exhibited greater tension at the start of the infusion but did not differ in tension reduction from HDs. These intercept level differences in sedation and tension may reflect allostatic differences in affective set points as a result of chronic alcohol use; these are often described in the literature as protracted withdrawal symptoms (Martinotti et al, 2008). Furthermore, ADs reported greater alcohol craving initially but their craving did not increase as rapidly as HDs' along rising BrACs.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, ADs exhibited greater tension at the start of the infusion but did not differ in tension reduction from HDs. These intercept level differences in sedation and tension may reflect allostatic differences in affective set points as a result of chronic alcohol use; these are often described in the literature as protracted withdrawal symptoms (Martinotti et al, 2008). Furthermore, ADs reported greater alcohol craving initially but their craving did not increase as rapidly as HDs' along rising BrACs.…”
Section: Discussionmentioning
confidence: 95%
“…Two of these studies, both of which used the SHAPS as their primary measure of anhedonia, found results consistent with a reduction in levels of anhedonia with increasing duration of abstinence (Martinotti et al, 2008b;Martinotti et al, 2011). Indeed, Martinotti et al (2011) found that this reduction in anhedonia could be significantly accelerated by daily treatment with acetyl-l-carnitine.…”
Section: Alcoholmentioning
confidence: 91%
“…The duration of the study treatment was relatively long (16 weeks) compared to other clinical trials on alcoholics. 35 Half of the treated participants satisfactorily achieved and maintained abstinence from alcohol throughout the study period. The parallel reduction in craving, as observed in OCDS and VAS mean scores, supports the possibility of a link between the mechanism of action of pregabalin and its clinical efficacy.…”
Section: Discussionmentioning
confidence: 96%
“…This profile is in contrast with the occurrence of discontinuation symptoms and rebound anxiety when therapeutic doses of BDZ are abruptly discontinued. 38,39 The treatment of alcohol withdrawal and protracted withdrawal syndromes 35 may represent a further factor to take into account as a possible mechanism of pregabalin efficacy, given the mean improvement of the withdrawal symptoms throughout the study period. This data confirms what has been previously shown by Becker and colleagues 40 in an animal model of ethanol dependence.…”
Section: Discussionmentioning
confidence: 99%